Study of Indian society A Sociological Analysis of Social Welfare and Social Work Education - Nagpaul, Hans (New Delhi, 1972)
The study is divided into nine chapters, with a bibliographical essay at the end. Essentially it undertakes a sociological analysis of social welfare in India, with special reference to social work education. In Chapter 1, the main theme is defined and formulated; it also discusses the various methods and sources of data; it further analyses some of the major elements of the sociological frame of reference. The remaining eight chapters are presented in three parts: part one consists of four chapters which are devoted to the discussion of the concept of culture as the societal context of social work, study of Indian culture, changing patterns of Indian society, and Indian social problems; part two undertakes an analytical survey of Indian social welfare, growth and development of social work education, and professionalization in social work. The need for the total re-organization of social work education consistent with the social, economic, and political conditions of Indian society is brought out forcefully. In the concluding part, social work education vis-a-vis Indian culture and society is highlighted. It is emphasized that the present system of education and the various specialities on which courses are being offered have failed to serve the needs of our society. The notion of culture variability is stressed with reference to the organization and development of social welfare services on the one hand and the formulation of suitable programmes of social work based on indigenous conditions on the other. In this context, a strong plea is made for de-emphasizing American social work concepts, methods, and study material which have been exercising all pervasive influence on Indian social work education during the past three decades.
Keywords: Sociology